Nutritional profile of preschool children of fisherman - Aneena E R (Department of Home Science, College of Horticulture, 2003)
The present study entitled ''Nutritional profile of preschool children of fishermen community" was conducted among 100 preschool children of 4-5 years age group in the coastal areas ofThrissur district. Information regarding the socio economic conditions of the fishermen community indicated that the majority of them were Hindus. Joint family system was found in most of the families High educational status was an out standing feature observed. Poor housing conditions and living facilities were observed in majority of the households. Majority of the families earned between Rs.1500-Rs.3000.Food consumption survey revealed that all of them were habitual non vegetarians and rice and roots and tubers were the staple foods used. Fish was the most frequently used food item Foods like green leafy vegetables, vegetables, meat and eggs were rarely included in the diet. Dietary profile of preschool children indicated that all the food groups were far below the RDA except for pulses and fish. The nutritional intake was, satisfactory with respect to protein, thiamine and riboflavin Energy intake was found to be below 70 percent of RDA. Other nutrients like calcium, vitamin A and vitamin C were also significantly low. Mild symptoms of vitamin A deficiency as manifested by pigmentation in the eyes is an important feature observed in clinical examination. Majority of them had dental carries due to poor oral hygiene. More than 40 percent of children showed severe height deficit for their age, which may be due to nutritional, and other environmental factors. However, as per weight for age classification most of the children were coming under grade I and grade II malnutrition that had a significant relation with their nutrient intake showing the prevalence of current malnutrition. Distribution of children based on the anthropometric indices also revealed the prevalence of moderate malnutrition among preschool children in this community. The present study reveals that nutritional status of preschool children of fishermen community is not less than the nutritional status of preschool children in other rural poor communities of Kerala.